Prevalence of Motor Impairments in Children with Acute Lymphoblastic Leukemia during Chemotherapy: A Systematic Review - Desti Elza Muslimah; Mega Hasanul Huda; Allenidekania Allenidekania; Ayu Widya Lestari (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2026)
Motor impairments are a frequent and disabling consequence of vincristine‑based chemotherapy in children with acute lymphoblastic leukemia (ALL). These deficits can compromise daily functioning and long‑term quality of life. This systematic review aimed to synthesize evidence on the prevalence and characteristics of motor impairments among pediatric ALL patients undergoing chemotherapy. A comprehensive search was conducted across PubMed, ScienceDirect, Scopus, ClinicalKey, and ClinicalKey Nursing, supplemented by citation tracking. Observational studies published up to May 2025 were screened using the PEOS framework. Ten eligible studies involving 580 children were included. Outcomes assessed encompassed fine motor precision, manual dexterity, coordination, balance, agility, and strength. Motor impairments were consistently reported across all studies, with prevalence varying by treatment phase and country. During induction, prevalence ranged from 48% (USA) to 62.5% (Netherlands). In consolidation, rates reached 75.5% (Colombia). The highest prevalence was observed in the maintenance phase, with Turkey reporting 83.9% overall impairment and specific deficits in fine motor integration (70.6%), strength (74.4%), and upper‑limb coordination (61.1%). Finland showed the lowest overall prevalence (31.8%). Motor impairments are common and persistent in children with ALL receiving vincristine‑based chemotherapy, particularly during the maintenance phase. These findings underscore the need for standardized monitoring protocols, early detection, and timely rehabilitation strategies to mitigate long‑term functional decline and optimize quality of life in pediatric oncology care.